A translational evaluation of renewal of inappropriate mealtime behavior. Issue 4 (23rd October 2019) - Ibañez, Vivian F.; Piazza, Cathleen C.; Peterson, Kathryn M.
Abstract : The term renewal describes the recurrence of previously extinguished behavior that occurs when the intervention context changes. Renewal has important clinical relevance as a paradigm for studying treatment relapse because context changes are necessary for generalization and maintenance of most intervention outcomes. The effects of context changes are particularly important during intervention for pediatric feeding disorders because children eat in a variety of contexts, and extinction is an empirically supported and often necessary intervention. Therefore, we used an ABA arrangement to test for renewal during intervention with 3 children diagnosed with a feeding disorder. The A phase was functional reinforcement of inappropriate mealtime behavior in a simulated home setting with the child's caregiver as feeder, B was function‐based extinction in a standard clinic setting with a therapist as feeder, and the return to the A phase was function‐based extinction in a simulated home setting with caregiver as feeder. Returning to Context A resulted in renewal of inappropriate mealtime behavior across children, despite the caregivers' continued implementation of function‐based extinction with high levels of integrity.